PERFORMANCE ANALYSIS OF SOLAR DRYING SYSTEM FOR MARINE PRODUCT OF OMAN - Kaithari, Dinesh Keloth (International Journal of Students’ Research in Technology & Management, 2015)
In Many countries use of solar drying system is the order in food processing to save vegetables, fruits, coffee, tea, meat, fish and other crops. Solar heating system or solar drying system to dry foods and other product can make the quality of the product to be much better. The process of drying is removal of moisture mostly to protect the product for long time. The availability of good source information is lacking in some countries where solar drying system for food is needed. This project presents the design and fabrication of suitable solar drying system for different fishes which needs drying for preservation. Also there will be analysis on different fishes in Oman. Black body radiation principle is used in this project for receive the heat from the sun. Solar drying system is requires two main things, heat and air flow. The design of this drying system taken care of the both heat and air velocity. The sun light is observed through the glass plate to the black color coated metal plate. The basic frame of the design is made up from of an insulating material (wood) of size 143cm x 53.5cm x 11.5cm, absorber plate sheet painted black of size 90cm x 50cm and a cover glass (6mm thickness) sizing 146cm x 53cm. Cool air enter from air inlet heat from chamber then worm the air cause and raise exit throw hot air exit. Ideally, the results gave as temperature between 45 CÂ° and 60 CÂ° in the chamber. The fish content of different weight depending on the type of the fish reducing about25% of moisture in three days of 10hours each day of drying.Â Works studied are catalogued with summaries.